Academic Reflection – The Matriarchs of the Home: Unspeakable Subjects in Times of Austerity - Koch, Insa (feminists@law, 2018)
Investigates the gendered effects of austerity politics with reference to the case of working class ‘matriarchs of family homes’ who find that contemporary British ‘welfare reforms’ are far from ‘neutral’. On the contrary, they target precisely those areas of life that working class mothers often remain responsible for: the family homes that constitute the domain for social reproduction. It is here then that we see at play what Nicola Lacey identifies in Unspeakable Subjects (1998) as a central move: a shift from ‘private to public patriarchy’ at the heart of welfare provision.